ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI USAHA BUDIDAYA IKAN GURAMI DI KECAMATAN SUMBERGEMPOL KABUPATEN TULUNGAGUNG - Putri Dewi Masitoh; Navita Maharani; Vifi Nurul Choirina (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study analyzes factors influencing production and income from gourami cultivation in Sumbergempol District, Tulungagung. Quantitative methods were used with a sample of 55 farmers from a total population of 116 people. Data were analyzed using multiple linear regression and cost-income analysis. The results showed that pond area, feed quantity, and fry had a positive and significant effect on production, while labor had a negative effect. For income, production costs and production quantity had a significant effect, while education and length of business were insignificant. The average income of farmers was Rp85,086,102 per cycle with an R/C ratio of 1.49, indicating this business was profitable. The study's conclusions emphasize the importance of cost efficiency and optimization of production factors. Suggestions include cost-saving strategies, government support through feed subsidies, and further research with more comprehensive variables for business sustainability.